Current problems of regulatory and legal security of the enrollment of citizens for military service during mobilization - Pravdyvets, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
Background. An analysis of the sufficiency of the regulatory and legal support of the organization and the recruitment of citizens for military service during mobilization was conducted. It was established that the organizational and legal mechanisms for the organization and implementation of the enrollment of citizens for military service during mobilization, as well as the provision and registration of deferments to conscripts during mobilization and during wartime in the territorial recruitment and social support centers are not defined. The corresponding normative legal acts, which are necessary for the performance of tasks in the territorial recruitment and social support centers, remain undeveloped, in particular regarding the organization and conduct of proceedings in cases of administrative offenses, issuance, accounting and storage of military accounting documents. Methods . The basis of the work is the method of meaningful analysis, with the help of which the adequacy of the regulatory and legal support of the organization and the conscription of citizens for military service during mobilization was analyzed. Results . Practical recommendations for improving the regulatory and legal support for the activity of territorial recruitment and social support centers are provided, as well as the content of the procedure for organizing and conducting the enrollment of citizens for military service during mobilization is proposed. The directions of further research on the improvement of the methodology of regulatory and legal support of the activities of the territorial centers of recruitment and social support have been determined. Conclusions. The lack of organizational and legal mechanisms for holding territorial recruitment centers and social support for the enrollment of citizens for military service during mobilization and issuing deferments to conscripts for the period of mobilization and military service has been confirmed, as well as other regulatory and legal acts that need to be developed and improved to ensure activities of territorial recruitment and social support centers.